Foreign exchange and international trade in Nigeria - Agene, Casimir Emman (Lagos : Gene Publications, 1991)
In this book the author's emphasis is on basic concepts and techniques of foreign exchange and international trade in Nigerian context. The book is intended for students who have a basic grounding in banking and finance. The book should also meet the needs of students reading finance and banking courses at polytechnics and universities -- Back Cover.
Includes bibliographical references and index.
rpm 02/09/2016
Loans
Keywords: Foreign exchange; Foreign exchange administration -- Nigeria; Financial institutions -- Nigeria; International trade; Money; International finance; Nigeria